Thermal expansion of single-crystal fullerite C60 at liquid-helium temperatures - Aleksandrovskii, A. N.; Esel`son, V. B.; Udovidchenko1, V. G. Manzheliiand B. G.; Udovidchenko, B. G.; Soldatov, A.; Sundqvist, B.; Soldatov, A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2000)
The thermal expansion of single crystal fullerite C60 has been studied in the range of liquid-helium temperatures (2-10 K). At temperatures below 4.5 K the thermal expansion of fullerite C60 becomes negative, in agreement with previous results on polycrystalline materials. A qualitative explanation of the results is proposed.